Pembangunan Dermaga di Pantai Pasir Kuning Tempilang Kabupaten Bangka Barat Kepualuan Bangka Belitung - Amelia Puspita Sari; Amelia Sari; Alfio Raldo; Andi Saputra; M. Afdal S. (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
The construction of the pier at Pasir Kuning Beach, Tempilang, West Bangka Regency, Bangka Belitung Islands, aims to improve access and facilities for visitors. The beach is famous for its yellow sand beauty and distinctive cultural attractions, such as the tradition of the Ketupat War. The planned pier will support tourism activities by providing facilities for tourist boats and improving safety in shipping. This study evaluates the technical and topographic aspects needed to determine the most appropriate location of the pier. By taking into account factors such as tides, waves, and currents, the optimal location for the construction of the pier was successfully identified. This study uses a quantitative descriptive method with secondary data collection and financial analysis involving parameters such as Net Present Value (NPV), Internal Rate of Return (IRR), Benefit Cost Ratio (BCR), and Payback Period (PP). The results of the analysis show that this project is financially feasible, with an NPV of IDR 2,664,366,232.32 (10% discount) and IDR 1,583,944,003.86 (15% discount), IRR of 13.1%, BCR of 1.4, and a payback time of 2.8 years. In addition, the project is expected to boost local economic growth through increasing the number of tourists and promoting local culture. Overall, this initiative not only focuses on the development of physical infrastructure but also on the development of tourism potential and the preservation of local culture, thus providing long-term benefits to the surrounding community.